Analysis of ferromanganese deposits from Mallorca, Spain - Prescott, D M (Supplement to: Prescott, DM (1988): The geochemistry and palaeoenvironmental significance of iron pisoliths and ferromanganese crusts from the Jurassic of Mallorca, Spain. Eclogae Geologicae Helvetiae, 81(2), 387-414, https://doi.org/10.5169/seals-166185, 1988)
The geochemistry of ferromanganese crusts and iron pisoliths from the Jurassic of Mallorca is investigated. The deposits are associated with Toarcian condensed sequences and hardgrounds which overlie Lower Lias platform limestones. Goethite is the principal mineral in the crusts and the pisoliths. which are both rich in iron; ramsdellite is the manganese phase in the ferromanganese crusts which contain 3-5% Mn. Inter-element relationships established by electron microprobe analysis show that P, V and perhaps Cr are sorbed with Fe, while Ni, Ti, Si and perhaps Ba and Co correlate positively with Mn. Submarine hydrothermal exhalations were the likely source of much of the material, though continental run-off waters probably contributed elements towards the growth of the ferromanganese crusts. Composition-depth curves suggest a gradual deepening of the drowned margin, though appear to over-estimate the depth of formation of the deposits. Deposition occurred on a limestone seamount on subsiding continental crust during the early rifting phase which preceded the opening of the Ligurian Tethys.